`x/(x^2-9) + (x+1)/(x^2+6x+9)` Perform the indicated operation(s) and simplify

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`x/(x^2-9)+(x+1)/(x^2+6x+9)`

Apply the following identities to factorize the denominators of the above rational functions:

`a^2-b^2=(a+b)(a-b)`  and

`a^2+2ab+b^2=(a+b)^2`

`x/(x^2-9)+(x+1)/(x^2+6x+9)=x/(x^2-3^2)+(x+1)/(x^2+2x(3)+3^2)`

`=x/((x+3)(x-3))+(x+1)/(x+3)^2`

LCD of the above expression is `(x-3)(x+3)^2`

`=(x(x+3)+(x+1)(x-3))/((x-3)(x+3)^2)` 

`=(x^2+3x+x^2-3x+x-3)/((x-3)(x+3)^2)`

Combine the like terms of the numerator,

`=(x^2+x^2+3x-3x+x-3)/((x-3)(x+3)^2)`

`=(2x^2+x-3)/((x-3)(x+3)^2)`

Factorize the numerator by splitting the middle term,

`=(2x^2-2x+3x-3)/((x-3)(x+3)^2)`

`=(2x(x-1)+3(x-1))/((x-3)(x+3)^2)`

`=((2x+3)(x-1))/((x-3)(x+3)^2)`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial